The influence of basalt fiber on the mechanical performance of concrete-filled steel tube short columns under axial compression - Wang, Xinzhong; Li, Linshu; Xiang, Yi; Wu, Yuexing; Wei, Mei (Frontiers in Materials, 2024)
With rapid economic and social development, both concrete-filled steel tube (CFST) composite structures and basalt fiber (BF) have been widely applied to the field of civil engineering. To investigate the laws and characteristics of the influence of chopped BF on the mechanical properties of CFST columns, and further promote the application of BF in CFST structures, the axial compressive bearing capacity test of 18 CFST short columns was carried out, and the influence of BF of different lengths on their structural mechanical properties was analyzed. The test results were compared with the theoretical calculation results and the finite element analysis results to verify the reasonableness of the test results. The results reveal that the axial compressive bearing capacity of the CFST short column with the addition of BF is significantly improved, compared to the ordinary CFST short column, in which the bearing capacity and the ductility coefficient is respectively increased by about 8.1 % and 31.6 % on average. In addition, changing the length of BF has less effect on the bearing capacity of CFST short columns, the rate of increase in bearing capacity decreases with the increase in steel ratio of CFST, while the coefficient of ductility increases with the increase in steel ratio.